Strategi Pemasaran Travel Haji Dan Umroh Dalam Meningkatkan Minat Jamaah (Studi PT. Amara Tour And Travel Tahun 2024 - Tiana, Rida; Tamyis, Tamyis; Fernadi, M. Feri (EL-EMIR Institute, 2025)
This study aims to analyze the marketing strategies implemented by PT. Amara Tour and Travel in increasing public interest in Hajj and Umrah services in 2024. Using a descriptive qualitative approach, data were collected through observation, in-depth interviews, and documentation. The findings reveal that PT. Amara’s marketing strategy is integrative, combining digital methods such as social media utilization, storytelling, and customer service technology with conventional approaches like community-based promotion through religious gatherings (majelis taklim) and alumni testimonials. This strategy effectively reaches various segments of prospective pilgrims and strengthens emotional bonds and public trust. Furthermore, the study identifies both strengths and weaknesses in PT. Amara’s marketing practices. Its strengths include a strong brand reputation, comprehensive service quality, and a spiritual approach that enhances customer loyalty. However, the company faces several challenges, such as limited promotional outreach in rural areas, a gap between promotional promises and service realities, and a shortage of human resources during peak registration periods. These findings highlight the need for continuous evaluation and innovation in marketing strategies to expand service coverage and improve customer satisfaction.